Lessons to be Learned from the European Unemployment of the 80s (The Quaid-i-Azam Lecture) (The Pakistan Development Review, 1989)
Economics as a science is aimed at dealing with specific phenomena. Its progress indeed comes from reflections and research works motivated by real problems. European unemployment of the 80s is a major fact today. Studying it and reflecting on it ought to be more generally rewarding for a scientific understanding of the economic phenomena. This is thus a topic that should interest economists around the world. Although it is well recognized, its significance may be underrated, in particular in North American universities, which play such a dominant role in what the profession talks about.' In order to induce a wider discussion of what ought to be learned from this recent historical experience, I shall first summarize the description of the phenomenon and the main explanation that has to be given of it. I shall then be in a position to consider the implications for building the macroeconomic theory. In the last section of this talk, and speaking more tentatively, I shall venture some conclusions for development economics.